Transfer of Training: Does It Truly Happen?: An Examination of Support, Instrumentality, Retention and Learner Readiness on the Transfer Motivation and Transfer of Training - Bhatti, Muhammad Awais; Battour, Mohamed Mohamed; Sundram, Veera Pandiyan Kaliani; Othman, Akmal Aini (Emerald Group Publishing Limited, 2024)
Purpose The purpose of this study is to highlight the importance of selected environmental, situational and individual factors in the training transfer process.